2023
DOI: 10.3389/fcimb.2022.1091341
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of blood microbiota in healthy individuals assessed by light and electron microscopy

Abstract: IntroductionThe blood microbiome is still an enigma. The existence of blood microbiota in clinically healthy individuals was proven during the last 50 years. Indirect evidence from radiometric analysis suggested the existence of living microbial forms in erythrocytes. Recently targeted nucleic acid sequencing demonstrated rich microbial biodiversity in the blood of clinically healthy individuals. The morphology and proliferation cycle of blood microbiota in peripheral blood mononuclear cells (PBMC) isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…myocardial infarction, chronic kidney disease, type 2 diabetes, and psoriasis. [34][35][36] A much higher load of circulating bacterial DNA was detected by PCR from CSU patients with nsAH resistance than those without or healthy subjects in our previous work. 10 The current study successfully identified the composition of circulating microbiota by 16s rDNA sequencing in the VDI group and found a remarkably high rate of nsAH resistance.…”
mentioning
confidence: 66%
“…myocardial infarction, chronic kidney disease, type 2 diabetes, and psoriasis. [34][35][36] A much higher load of circulating bacterial DNA was detected by PCR from CSU patients with nsAH resistance than those without or healthy subjects in our previous work. 10 The current study successfully identified the composition of circulating microbiota by 16s rDNA sequencing in the VDI group and found a remarkably high rate of nsAH resistance.…”
mentioning
confidence: 66%
“…In fact, the existence of blood microbiota in clinically healthy individuals was proven during the last 50 years. Indeed, indirect evidence by radiometric analyses suggested the existence of living microbial forms in erythrocytes [25]. In addition, the observation of the PP‐Spike marker in individuals vaccinated more than 30 days after the vaccine in about 50% of subjects could also be explained by the wide biodiversity of eukaryotic and prokaryotic microbiota identified in blood by next‐generation sequencing technologies [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of dark field microscopy techniques, fluorescent in situ hybridization, and flow cytometry led to the identification of pleomorphic bacteria in the blood, capable of altering their characteristics in response to environmental conditions [ 7 ]. Moreover, the analysis of blood microbiome morphology in peripheral blood mononuclear cells (PBMCs) using light and electron microscopy highlighted how the blood microbiome displays a complex life cycle, undergoing different morphological transformations, such as vesiculation, tabulation, budding, irregular binary fission, and protrusion–extrusion of progeny cells from large electron-dense bodies [ 8 ]. Recently, several studies have managed to increase the “power” of analysis due to a lower abundance of bacterial DNA, investigating healthy blood microbial taxonomy, identifying the most abundant phyla, and sometimes also bacterial genera [ 9 ] using 16 s rRNA gene sequencing technology [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%